Intermediary balance sheets and the treasury yield curve - Wenxin Du; Benjamin Hébert; Wenhao Li (Federal Reserve Bank of New York, 2022)
We have documented a regime change in the U.S. Treasury market post-Global Financial Crisis (GFC). We first derived bounds on Treasury yields that account for dealer balance sheet costs, which we call the net short and net long curves. We show that actual Treasury yields moved from the net short curve pre- GFC to the net long curve post-GFC, consistent with the shift in the dealers' net position. We then use a stylized model to demonstrate that increased bond supply and tightening leverage constraints can explain this change in regime. This change, in turn, helps explain negative swap spreads and the co-movement between swap spreads, dealer positions, yield curve slope, and covered-interest-parity violations, and implies changing effects for a wide range of monetary and regulatory policy interventions.
Keywords: G12; E52; F3; 330; yield curve; balance sheet constraints; CIP deviations; Staatspapier; Öffentliche Anleihe; Zinsstruktur; Finanzkrise; Internationaler Finanzmarkt; Geldpolitik; Zentralbank; USA